T-Bet Controls Cellularity of Intestinal Group 3 Innate Lymphoid Cells - Schroeder, Jan-Hendrik; Meissl, Katrin; Hromadová, Dominika; Lo, Jonathan W.; Neves, Joana F.; Howard, Jane K.; Helmby, Helena; Powell, Nick; Strobl, Birgit; Lord, Graham M. (Frontiers in Immunology, 2021)
Innate lymphoid cells (ILC) play a significant immunological role at mucosal surfaces alike the intestine. T-bet-expressing group 1 innate lymphoid cells (ILC1) are believed to play a substantial role in inflammatory bowel disease (IBD). However, a role of T-bet-negative ILC3 in driving colitis has also been suggested in mouse models questioning T-bet as a critical factor for IBD. We report here that T-bet deficient mice had a greater cellularity of NKp46-negative ILC3 correlating with enhanced expression of RORγt and IL-7R, but independent of signalling through STAT1 or STAT4. We observed enhanced neutrophilia in the colonic lamina propria (cLP) of these animals, however, we did not detect a greater risk of T-bet-deficient mice to develop spontaneous colitis. Furthermore, by utilising an in vivo fate-mapping approach, we identified a population of T-bet-positive precursors in NKp46-negative ILC3s. These data suggest that T-bet controls ILC3 cellularity, but does do not drive a pathogenic role of ILC3 in mice with a conventional specific pathogen-free microbiota.